Local energy decay for the damped Klein-Gordon equation in exterior domain. Issue 2 (25th January 2017) - Malloug, Mohamed
Abstract : We prove uniform local energy decay for the solution of the dissipative Klein–Gordon equation on an exterior domain under some geometric condition called "exterior geometric control".